Search for FCNC single top-quark production at √s=7 TeV with the ATLAS detector - Aad, G; Abbott, B; Abdallah, J; Abdelalim, A; Abdesselam, A; Abdinov, O; Abi, B; Abolins, M; AbouZeid, O; Abramowicz, H; Abreu, H; Acerbi, E; et al. (2012)
A search for the production of single top-quarks via flavour-changing neutral-currents is presented. Data collected with the ATLAS detector at a centre-of-mass energy of √s=7 TeV, corresponding to an integrated luminosity of 2.05 fb-1, are used. Candidate events with a semileptonic top-quark decay signature are classified as signal- or background-like events by using several kinematic variables as input to a neural network. No signal is observed in the neural network output distribution and a Bayesian upper limit is placed on the production cross-section. The observed upper limit at 95% confidence level on the cross-section multiplied by the t→Wb branching fraction is measured to be σqg→t×B(t→Wb)<3.9 pb. This upper limit is converted using a model-independent approach into upper limits on the coupling strengths κugt/Λ<6.9{dot operator}10-3 TeV-1 and κcgt/Λ<1.6{dot operator}10-2 TeV-1, where Λ is the new physics scale, and on the branching fractions B(t→ug)<5.7{dot operator}10-5 and B(t→cg)<2.7{dot operator}10-4. © 2012 CERN.